Improving awareness, knowledge and attitude of epilepsy using an interactive animated epilepsy education programme (IAEEP) among Malaysian teachers and students - Fong, Choong Yi; Foo, Jen Chun; Kong, Ann Nie; Rithauddin, Ahmad Mohamed; Adnan, Azirah; Lua, Pei Lin; Ng, Kher Hui (ASEAN Neurological Association, 2018)
Background: Improving awareness, knowledge and attittude (AKA) of teachers and students about epilepsy is an important step to reduce the stigma experienced by children with epilepsy. To date there are no studies evaluating effectiveness of an information technology based epilepsy education programme in improving AKA among teachers and students. Method: Cross-sectional study was to assess the baseline AKA of epilepsy among Malaysian teachers and secondary school students, and to examine effectiveness improving their AKA using the Interactive Animated Epilepsy Education Programme (IAEEP). AKA of teachers and students were assessed pre-and post-implementation of IAEEP. Results: Total of 54 teachers and 67 secondary students participated in this study. The baseline AKA on epilepsy among Malaysian teachers was low in the awareness domain, moderate in the knowledge domain, and positive in the attitude domain. The baseline AKA on epilepsy among students was very low in the awareness domain, low in the knowledge domain, and indifferent in the attitude domain. The AKA scores in all domains of teachers and students improved significantly after introduction of IAEEP (P<0.001). Post-IAEEP the AKA of teachers was moderate in the awareness domain, high in the knowledge domain, and very positive in the attitude domain; the AKA of students was low in the awareness domain, very high in the knowledge domain, and very positive in the attitude domain Conclusion: Our findings highlight a need for epilepsy educational programmes to be implemented in Malaysian schools. The IAEEP is an effective educational programme to improve the AKA particularly in the knowledge domain among teachers and students.